Between Commemoration and Living Memory: Symbolic Acts of the Teutonic Knights in Light of Cultural Theory - Youmans, Nicholas W. (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2021)
The present article investigates the function of ritual acts as a form of communication vis-à-vis cultural meaning in the life of the Teutonic Knights. As a condensed form of communal expression, rituals exhibit an acute potential to render present collective identity and shape the lives of the communities that practice them. Such potential is manifest in the institutional arrangement of the Teutonic Order in various forms with particular reference to their dual standing in society, insofar as they drew upon the societal models of the oratores and the bellatores. Particularly relevant to the current study, considerations of cultural historian and social analyst Jan Assmann regarding symbolic acts and collective living memory assist in creating the theoretical framework for the study’s deliberations. With Assmann’s insights in mind, ritual is understood as a communicative vector of cultural meaning – so to speak – of living memory. The analysis then turns to an examination of select representative examples from diverse scenarios in the existence of the Teutonic Knights, thereby taking into account internal, public, and participatory contexts of symbolic moments. The study thus explores how, while rituals can commemorate memorialised events from the past, they are also able to enact the living memory of a collective entity, ultimately claiming that the examined symbolic acts exhibited both communicative and transformative potential.